2021
DOI: 10.1038/s41598-021-02576-6
|View full text |Cite
|
Sign up to set email alerts
|

An insight into thermal properties of BC3-graphene hetero-nanosheets: a molecular dynamics study

Abstract: Simulation of thermal properties of graphene hetero-nanosheets is a key step in understanding their performance in nano-electronics where thermal loads and shocks are highly likely. Herein we combine graphene and boron-carbide nanosheets (BC3N) heterogeneous structures to obtain BC3N-graphene hetero-nanosheet (BC3GrHs) as a model semiconductor with tunable properties. Poor thermal properties of such heterostructures would curb their long-term practice. BC3GrHs may be imperfect with grain boundaries comprising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Figure 5 depicts the temperature profile of a graphene/biphenylene hybrid nanoribbon with a length of 24 nm at room temperature and a temperature gradient of 40 K. The temperature profile of this hybrid nanoribbon exhibits a discontinuity at the interface position (placed in the middle) at which a significant temperature drop is recorded. This effect is attributed to the variation of atomic structure at the two sides of the interface which causes phonon scattering and consequently a temperature drop (T g ), which for our case equals to 18.4 K [30]. A similar behavior in the steady-state temperature profile for graphene-boron nitride heterostructure across its interface was reported by Li et al [31].…”
Section: Heat Transport In Graphene/biphenylene Hybrid Nanoribbonsupporting
confidence: 85%
“…Figure 5 depicts the temperature profile of a graphene/biphenylene hybrid nanoribbon with a length of 24 nm at room temperature and a temperature gradient of 40 K. The temperature profile of this hybrid nanoribbon exhibits a discontinuity at the interface position (placed in the middle) at which a significant temperature drop is recorded. This effect is attributed to the variation of atomic structure at the two sides of the interface which causes phonon scattering and consequently a temperature drop (T g ), which for our case equals to 18.4 K [30]. A similar behavior in the steady-state temperature profile for graphene-boron nitride heterostructure across its interface was reported by Li et al [31].…”
Section: Heat Transport In Graphene/biphenylene Hybrid Nanoribbonsupporting
confidence: 85%
“…Certain studies have shown that graphene nanocomposites exhibit a relatively low percolation threshold and more optimized electrical conductivity than CNT 23 . Generally, the high surface energy of graphene and their strong interactions attenuate their uniform dispersal in the polymer medium [24][25][26][27][28] .The conductivity of nanocomposites is commonly governed by the concentration, dimensions, conductivity, and dispersion features of nanoparticles 29,30 . Many models have been developed to assume the effects of various variables, such as polymer-filler interfacial energy (affecting dispersion level), tunneling effect, agglomeration, and waviness on the conductivity of polymer nanocomposites [31][32][33][34][35][36][37] .…”
mentioning
confidence: 99%
“…Certain studies have shown that graphene nanocomposites exhibit a relatively low percolation threshold and more optimized electrical conductivity than CNT 23 . Generally, the high surface energy of graphene and their strong interactions attenuate their uniform dispersal in the polymer medium [24][25][26][27][28] .…”
mentioning
confidence: 99%